Students Critical Thinking Skill in Solving Scientific Literacy using a Metacognitive Test Based on Scientific Literacy - Pamungkas, Zakaria Sandy; Aminah, Nonoh Siti; Nurosyid, Fahru (Jurnal Ilmiah Pendidikan Fisika Al-Biruni, 2018)
The purpose of this research is to measure students critical thinking skill in solving scientific literacy using a metacognitive test based on scientific literacy. This research is descriptive research. The subject of this research is 99 students of grade XI in SMA Batik 2 Surakarta. Data collection methods used are test methods which using a metacognitive test based on scientific literacy. Data analysis techniques use quantitative descriptive analysis. The results showed that the achievement of scientific literacy is still low at below 50% for all category. This is due to students critical thinking skill in solving all category of scientific literacy problem is still low. Low student critical thinking skill in solving science as a body of knowledge in the assessment stage with the percentage achievement is 21%. Low percentage achievement of critical thinking skill in solving science as a way of thinking is a clarification (34%), assessment (46%), inference (26%), and strategy (12%). Low percentage achievement of critical thinking skill in solving science as a way of investigating is assessment (39%), inference (5%), and strategy (6%). Low student critical thinking skill in solving science as an interaction between technology and society in the assessment stage with the percentage achievement is 31%